Effect Of Different Hygenic Condition During Milking On Bacterial Count Of Cows Milk - Islam, MA; Islam, MN; Khan, MAS; Rashid, MH; Obaidullah, SM (Bangladesh Journal of Animal Science, 2012)
Effect of three hygienic conditions (T1- washing and disinfection of udder and teats, milker hands, and a sanitary rinse of milking pails using calcium hypochlorite solution with 200 ppm Cl; T2- washing of udder and teats, milker hands and milking pails with normal water; and T3- without any kind of preparation of udder and teats, milker hands and milking pails) before milking were studied. Fifteen “Red Chittagong” milking cows were selected and divided into the three treatment groups (5 in each) maintaining under identical management conditions icluding floor hygiene, feeding and post-milking equipment sanitation. Initial bacterial quality as measured by Standard Plate Count (SPC), Coliform Count (CC) and Methylene Blue Reduction Time (MBRT) of milks obtained under T1,T2 and T3 were significantly (P<0.01) different. On the basis of SPC, CC and MBRT initial bacterial load was highest for T2-- milk and lowest for T1-- milk Initial SPC of T1 was 86% and 64% lower than that of T2 and T3 respectively, whereas CC of T1 was 89% and 69% lower than that of T2 and T3, respectively. Standard Plate Count and CC of T3 were respectively 43% and 65% lower than those of T1. The initial MBR time were in the order T1= T3>T2(P<0.01). Results of the present study revealed that milking hygiene has significant effect on initial bacterial count of milk. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9919 BJAS 2009; 38(1-2): 108-114